Мiнiзонна електропровiднiсть у надґратках сферичних квантових точок гетеросистеми InAs/GaAs - Boichuk, V. I.; Bilynskyi, I. V.; Pazyuk, R. I. (Publishing house "Academperiodika", 2018)
The electrical properties of nanoscale semiconductor InAs/GaAs heterosystems with 2D-superlattices of spherical quantum dots have been studied. The dependences of the electron group velocity on the wave vector and the miniband quantum number are obtained. The dependences of the Fermi level of electrons in minibands on the concentration of donor impurities, donor energy, and temperature are found. The temperature dependences of the majority carrier concentration and the electrical conductivity are analyzed for various donor concentrations and energies.